Liver Cancer–Specific Serine Protease Inhibitor Kazal Is a Potentially Novel Biomarker for the Early Detection of Hepatocellular Carcinoma. Issue 12 (23rd December 2020) - Lu, Felix; Shah, Pir Ahmad; Rao, Abhishek; Gifford-Hollingsworth, Cynthia; Chen, Anne; Trey, Gary; Soryal, Mina; Talat, Arslan; Aslam, Aysha; Nasir, Bilal; Choudhry, Saad; Ishtiaq, Rizwan; et al.
Abstract : INTRODUCTION: Liver cancer–secreted serine protease inhibitor Kazal (LC-SPIK) is a protein that is specifically elevated in cases of hepatocellular carcinoma (HCC). We assessed the performance of LC-SPIK in detecting HCC, including its early stages, in patients with cirrhosis, hepatitis B virus (HBV), and hepatitis C virus (HCV). METHODS: We enrolled 488 patients, including 164 HCC patients (81 early HCC) and 324 controls in a blinded, prospective, case–control study. Serum LC-SPIK levels were determined by an enzyme-linked immunosorbent assay-based assay. The performance of serum LC-SPIK and α-fetoprotein (AFP), including area under the curve (AUC), sensitivity, and specificity, are compared. The performance of LC-SPIK was evaluated in an independent validation cohort with 102 patients. RESULTS: In distinguishing all HCC patients from those with cirrhosis and chronic HBV/HCV, LC-SPIK had an AUC of 0.87, with 80% sensitivity and 90% specificity using a cutoff of 21.5 ng/mL. This is significantly higher than AFP, which had an AUC of 0.70 and 52% sensitivity and 86% specificity using a standard cutoff value of 20.0 ng/mL. For early-stage HCC (Barcelona Clinic Liver Cancer stage 0 and A), LC-SPIK had an AUC of 0.85, with 72% sensitivity and 90% specificity, compared with AFP, which had an AUC of 0.61, with 42% sensitivity and 86% specificity. In addition, LC-SPIK accurately detected the presence of HCC in more than 70% of HCC patients with false-negative AFP results. DISCUSSION: The study provided strong evidence that LC-SPIK detects HCC, including early-stage HCC, with high sensitivity and specificity, and might be useful for surveillance in cirrhotic and chronic HBV/HCV patients, who are at an elevated risk of developing HCC.